USING ROLEPLAYING AS AN INTERACTIVE METHOD TO BOOST SPEAKING IN EFL LESSONS AT UNIVERSITY - Smelianska, V.; Davydenko, O.; Ponomarenko, O. (Видавництво НДУ ім. М. Гоголя, 2024)
This article explores the potential of role-plays to improve oral interaction skills among junior English as a Foreign Language (EFL) learners enrolled in a higher language education program. The study is grounded in the theoretical foundations of interactive foreign language teaching technologies and the concept of communicative competence. The analysis revealed that role-plays when implemented strategically, can foster a supportive learning environment and promote the development of oral interaction subskills. Key recommendations for incorporating this interactive method include: (1) selecting engaging and relevant topics that resonate with students’ potential real-world experiences to heighten motivation and engagement; (2) utilizing role cards with clearly defined objectives and providing pre-task input on relevant vocabulary and grammar to empower students and reduce performance anxiety; (3) encouraging small group discussions before role-playing activities to create a safe space for practice and foster collaboration among learners; and (4) regularly incorporating role-playing into the curriculum to contribute to the ongoing development of speaking fluency, particularly dialogues, and collaborative communication skills. The article also presented sample activities designed for university-level EFL learners, covering topics such as introductions, making complaints, and personal experiences. These examples illustrate the practical application of the discussed method within the English as a foreign language lesson. In conclusion, this study’s findings suggest that the role-playing method aims to enhance oral interaction skills among EFL learners in higher education settings. By incorporating the recommendations outlined in this article, instructors can create a dynamic and engaging learning environment that fosters effective communication skill development. Further research is needed to explore the possibilities of using other interactive methods to develop EFL communicative competence in English as a foreign language lesson in higher language education students.
Keywords: interactive technologies; "role-playing" method; English speaking; dialogue; foreign language communicative competence; English as a foreign language lesson; higher language school